THE INFLUENCE OF FOOD INFLUENCERS ON CULINARY PURCHASE INTENTION - Azis, Saipul; Habibi, Roihan; Supriyadi, Ilham; Ikhsan, Ainul; Akbar, Anton; Candra, Dul (UIN Raden Mas Said Surakarta, 2025)
This study aims to analyze the influence of food influencers in Padang, specifically examining three credibility dimensions: attractiveness, trustworthiness, and expertise, on consumer purchase intention in the culinary sector. This research is motivated by the importance of understanding influencer effectiveness in the digital era, which is driven by